A107 PERCEPTION OF HEALTH AND ACCESSIBILITY IN AMAZONIA: an approach with GIS mapping to making decision on hospital location. Issue 2 (June 2015) - Tobias, Maisa; Silva, Nathalia; Rodrigues, Daniel
Abstract: Background: Processes of city planning have often supported decision-making methods that involve selection, evaluation and combination of several factors. In addition, nowadays, the accessibility is one important issue for the development of cities. Therefore, factors closely related to the accessibility are very relevant to identify and assess the location of urban facilities, which stresses the interest of evaluating accessibility methods. The main goal of the paper is to present an accessibility analysis applied in a hospital of Santarem, in Brazil, a city located midway between the larger cities of Belem and Manaus. In 2007, The Low Amazonas Regional Public Hospital (LARP Hospital) located in the city of Santarem aiming to decentralize the state health service, taking to the western of Para one reference hospital specialized in medium and high complexity service. Despite the large extension of Low Amazonas region, this area has received unsatisfactory attention in health studies. Methods: The paper describes the research instruments, sampling method and data analysis proposed for mapping urban accessibility in health of LARP Hospital in relation to Santarem and other cities in its surrounding, as the main key-destinations. In this sense, the goal of this research was to analyze the accessibility of the LARP Hospital as reference center, what became possible by the georeferencing and interviews with 381 LARP users, considering confidence level of 95% and margin of error of 5%, using a four-part questionnaire: travel pattern; socioeconomics input; service evaluation and main destinations. The model was implemented within a Geographic Information System (GIS) and integrates the individual's perspective, through the definition of each key destination weight, reflecting their significance for daily activities in health in the region. Results: The main options accessibility of the LARP hospital is lowering. Therefore, this justifies the construction of the second high complexity hospital in order to minimize the iniquities of the public health service in the region. Health services in the Lower Amazon is inaccessible for much of the population, mainly by the presence of physical barriers to health, either by distance or by the lack of available means of transport. Conclusions: The results of this model application can support city administration decision-making for new investments in order to improve urban quality of live. In addition, the model can simulate and analyze several planning proposal for the city, e.g., expansion of the transport network, the construction of new health services, helping to understand which will be the consequences of those actions.